Martin Chuzzlewit - Dickens, Charles, 1812-1870. (Oxford ; New York : Oxford University Press, 1990)
At the center of Martin Chuzzlewit is Martin himself, very old, very rich, very much on his guard. What he suspects (with good reason) is that every one of his close and distant relations, now converging in droves on the country inn where they believe he is dying, will stop at nothing to become the inheritor of his great fortune. Having unjustly disinherited his grandson, young Martin, the old fellow now trusts no one but Mary Graham, the pretty girl hired as his companion. Though she has been made to understand she will not inherit a penny, she remains old Chuzzlewits only ally. As the viperish relations and hangers-on close in on him, we meet some of Dickenss most marvelous characters - among them Mr. Pecksniff (whose name has entered the language as a synonym for ultimate hypocrisy and self-importance): the fabulously evil Jonas Chuzzlewit: the strutting reptile Tigg Montague: and the ridiculous, terrible, comical Sairey Gamp.
Keywords: British -- United States; Fiction; Grandfathers -- Fiction; Young men -- Fiction; Avarice -- Fiction; United States -- Description and travel; Fiction; England -- Fiction; Classic Literature; Bildungsromans; Black humor